Where is the Oxygen? Structural Analysis of α‐Humulene Oxidation Products by the Crystalline Sponge Method1. Issue 31 (12th June 2015) - Zigon, Nicolas; Hoshino, Manabu; Yoshioka, Shota; Inokuma, Yasuhide; Fujita, Makoto
Abstract Crystal structures of α‐humulene, a cyclic sesquiterpene, and its oxidized subproducts, were analyzed by the crystalline sponge method. Regio‐ and stereochemistry, including absolute configuration when a chiral oxidant was applied, and the stable conformations of all the scaffold‐related compounds were successfully determined for samples on a 5–50 μg scale.